2022
DOI: 10.1163/22134808-bja10072
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Perception and Learning: Linking Pedagogy, Psychophysics, and Human–Computer Interaction

Abstract: In this review, we discuss how specific sensory channels can mediate the learning of properties of the environment. In recent years, schools have increasingly been using multisensory technology for teaching. However, it still needs to be sufficiently grounded in neuroscientific and pedagogical evidence. Researchers have recently renewed understanding around the role of communication between sensory modalities during development. In the current review, we outline four principles that will aid technological deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The simultaneous use of the senses creates a stimulating experience that effectively captures the recipient's attention and produces more intense emotions. As a result, information retention is enhanced ( 41 ) and a lasting experience is generated, creating an emotional connection with the recipient ( 31 ). Furthermore, a study by Rolls et al ( 38 ), reported a link between visual, olfactory and auditory stimuli and the learning process, as both the amygdala and the hippocampus interact with the emotion produced by the stimulus, generating learning that is demonstrated in social and emotional behavior ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous use of the senses creates a stimulating experience that effectively captures the recipient's attention and produces more intense emotions. As a result, information retention is enhanced ( 41 ) and a lasting experience is generated, creating an emotional connection with the recipient ( 31 ). Furthermore, a study by Rolls et al ( 38 ), reported a link between visual, olfactory and auditory stimuli and the learning process, as both the amygdala and the hippocampus interact with the emotion produced by the stimulus, generating learning that is demonstrated in social and emotional behavior ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intelligent control model, based on gesture and speech interaction, has effectively promoted the rapid development and updating of human-computer interaction in education management. It also provides a more efficient means for educational management [6][7].…”
Section: Introductionmentioning
confidence: 99%